Sexual dimorphism and morphometric characterization of Centris tarsata Smith, 1874, Hymenoptera: Apidae in different environments - Adriane Vieira Souza; Lorena Andrade Nunes; Cerilene Santiago Machado; Geni da Silva Sodré; Carlos Alfredo Lopes de Carvalho (Acta Agronómica)
Solitary bees Apidae: Centridini are important pollinators of Malpighia emarginata DC. Malpighiales: Malpighiaceae. However, there are few studies on the characterization of populations of this species in areas with orchards and their surroundings. This study analyzed the morphometric variability and sexual dimorphism of Centris tarsata Smith, sampled in artificial nests installed at four different vegetation types. The right forewings of 168 individuals were dissected, photographed, and the images processed in TpsUtil and brought to the TpsDig2 version 2.12 for plotting 18 landmarks by geometric morphometrics. Data were analyzed through Principal Components Analysis PCA, Canonical Variables CV, and cross-validation in order to test the correct classification of each individual in the CV. In addition, the size analysis through the centroid size was used and subsequently the univariate analysis ANOVA and Tukey test were conducted. Different environmental conditions may influence the morphometric intrassexual pattern of C. tarsata and promote sexual selection. Sexual dimorphism of C. tarsata was observed, which can be a determining factor to favor distinct biological characteristics in an evolutionary process, supporting the understanding of ecological, biological, morphogenetic, and behavioral factors in the agro-ecosystem.